Painful locking of the wrist in a patient with pseudoachondroplasia confirmed by COMP mutation. Issue 1 (2nd January 2017) - Ideta, Hirokazu; Uchiyama, Shigeharu; Hayashi, Masanori; Kosho, Tomoki; Nakamura, Yukio; Kato, Hiroyuki
Abstract: We report the case of a 40-year-old woman with pseudoachondroplasia (PSACH), with a heterozygous mutation (c.806A > G, p.Asp269Gly) located in the Type 3 repeats domain of the cartilage oligomeric matrix protein gene, who complained of the unusual symptom of painful locking of the wrist. Her condition was caused by a non-traumatic enlargement of the extensor carpi radialis longus (ECRL) and brevis (ECRB) tendons along with bulbous swelling of the synoviums around them. Surgical treatment resolved these unusual tendon-related symptoms. Repetitive mechanical loading of the wrist in daily activities, including distal intersection tenosynovitis between the extensor pollicis longus tendon and ECRL and ECRB tendons, may have contributed to changes in the structural integrity of the tendons. We should pay more attention to tendon-related symptoms in patients with PSACH.